The Effect Of Health Education On The Level Of Family Knowledge About First Aid For Stage 1 Hypertension Patients In The Puskesmas Working Area - Basrizal Basrizal (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
This study aims to determine whether first aid for stage 1 hypertension in the working area of the Krueng Barona Jaya District Health Center is still relatively low, so it is necessary to increase family knowledge by conducting health education about first aid for stage 1 hypertension. Objectives: To identify the effect of health education on the level of family knowledge about first aid for patients with stage 1 hypertension. Methods: The research design used the Quasi Experiment method with a pre-test and post-test non equivalent control group approach using a questionnaire measuring instrument with purposive sampling technique. The number of samples taken was 36 families with stage hypertension. Results: The results obtained that after being given health education about first aid for stage 1 hypertension, family knowledge is good. Analysis: the results obtained by the majority after being given health education family knowledge is good. A total of 32 respondents (89%) who have good knowledge, 4 respondents (11%) have sufficient knowledge and no respondents have poor knowledge. Using the Paired Sample t-test test shows a significant number between pretest and posttest scores with a significance value (2 failed) p = 0.000 <0.005 so that H0 is rejected and Ha is accepted. Discussion: Health education has a very important role in determining human quality, with health education humans gain knowledge and information. The higher a person's level of knowledge, the higher the quality of life.